If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1x = 9 Solving 12 + -1x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 9 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 9 + -12 -1x = 9 + -12 Combine like terms: 9 + -12 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 6x+6=-34-4x | | 24=2m | | 2x+[x+3]=24 | | 33.7-(1.5s+2.3)=3.4-(0.4-5.7s) | | 5+4p=-7 | | 5x+4=x+20 | | -6z+4(z+3)=-2z+14 | | 6x+141=5x-3 | | XY+Y= | | -13+13=0 | | 5x-2(4+4x)=11 | | -4(4+7n)+5(3+4n)=-5n-2n | | a^4-7a^2+10=0 | | 9x-8=3x+4 | | 165+20x=180 | | -6n=2m+3 | | -4(4+7n)+5(3+4n)=-5-2n | | 15v-9v=42 | | y=-2(5)+2 | | x+2x+[x+3]=23 | | y-11=-27 | | 17x-10x=-6 | | 10z-6=4z-15-3z | | 15+20x=180 | | 140795*100/145= | | 6X+1+.05=252 | | 4x+10y=100 | | a^2-7a^2+10=0 | | 10y+10=90 | | 16(2x-8)=4(8x+9) | | 3b-(13)+4b=7b+1 | | -20=-5+3(y-5) |